Advances in microbial food safety. - Sofos, John Nikolaos (Woodhead Publishing in food science, technology, and nutrition, 2015)
Research and legislation in food microbiology continue to evolve, and outbreaks of foodborne disease place further pressure on the industry to provide microbiologically safe products. This second volume in the series Advances in Microbial Food Safety summarises major recent advances in this field, and complements volume 1 to provide an essential overview of developments in food microbiology. Part one opens the book with an interview with a food safety expert. Part two provides updates on single pathogens, and part three looks at pathogen detection, identification and surveillance. Part four covers pathogen control and food preservation. Finally, part five focuses on pathogen control management.